Effect of liquid diffusion and segregation on GFRP insulation performance in typical hygrothermal environment. (September 2022) - Xie, Qing; Duan, Qijun; Xia, Guowei; Li, Jingwei; Yin, Kai; Xie, Jun
Abstract : Glass fiber reinforced polymer (GFRP) insulation materials widely used in the field of the high voltage transmission will suffer serious performance degradation in hygrothermal environment. In this paper, the effect of liquid diffusion on GFRP insulation performance in three typical hygrothermal environments is studied by experiments and molecular dynamics (MD) simulation. The insulation performance test results show that the insulation properties of GFRP will seriously deteriorate in different hygrothermal environments, and the deterioration of samples in salt spray and acid rain presents significant phase variation. The "segregation" effect of solute particles in salt spray and acid rain is revealed by MD simulation and micro-characterization. Sodium chloride tends to diffuse and accumulate at the interface, resulting in fiber peeling and multi-stage decline in insulation properties. Acid rain is easy to corrode the epoxy resin (EP), and the deep trap introduced by the reaction will inhibit the development of discharge, leading to a quasi-periodic fluctuation degradation in the insulation performance. In addition, there is a competitive effect between solute particles and water molecules, which will prevent the diffusion of moisture. The research provides a basis for revealing the deterioration mechanism of GFRP insulation in different hygrothermal environments. It also has reference significance for the targeted modification of GFRP against hydrothermal aging. Highlights: There are obvious differences in the insulation degradation laws of GFRP in salt spray, acid rain and deionized water. We introduce the "segregation" to explain the difference in insulation degradation laws. The segregation and competition effects of liquid particles are proved based on characterization and simulation. The results are of great significance for understanding the hygrothermal aging characteristics of GFRP.